Co-assembly of egg white-derived peptides and protein-polysaccharide complexes for curcumin encapsulation: The enhancement of stability, redispersibility, and bioactivity. (15th November 2022) - Li, Yajuan; Liu, Jingbo; Ma, Sitong; Yang, Meng; Zhang, Hui; Zhang, Ting; Yu, Yiding; Du, Zhiyang
Graphical abstract: Highlights: EWDP could self-assemble a well-defined structure based on the CA-HTCC complexes. EWDP could provide additional hydrophobic cavities for CA-HTCC complexes. EWDP reinforced the physio-chemical stability of Cur loaded CA-HTCC complexes. EWDP exhibit the potential synergistic effect with Cur by enhancing its solubility. EWDP could widen the application of protein-polysaccharide based delivery systems. Abstract: In this study, a nanocomposite was developed by introducing egg white-derived peptides (EWDP) into protein-polysaccharide complexes to trigger the self-assembly of EWDP for encapsulating curcumin (Cur) via the pH-driven method. In this system, EWDP could cooperate with protein-polysaccharide complexes to exert superior colloidal properties with excellent Cur aqueous solubility, redispersibility, and physical stability and act as a bioactivity amplifier to endow the delivery system with the synergistic antioxidant activity. This phenomenon was ascribed to the additional hydrophobic cavities, hydrogen bonding, and electrostatic interactions organized by EWDP. Additionally, the presence of EWDP could considerably boost the cellular antioxidant activity of Cur by decreasing reactive oxygen species (ROS) levels, improving free radical scavenging capacity, and recovering the activity of endogenous antioxidant enzymes. These findings might open up an avenue to reinforce lipophilic nutraceuticals' physicochemical properties and functionalities based on the co-assembly of food-derived peptides and protein-polysaccharide complexes.